Design, fabrication, and test of bi-functional metalenses for the spin-dependent OAM shift of optical vortices - Vogliardi, Andrea; Bonaldo, Daniele; Dal Zilio, Simone; Romanato, Filippo; Ruffato, Gianluca (Frontiers in Physics, 2024)
The ability to encode different operations into a single miniaturized optical device is required to reduce the complexity and size of optical paths for light manipulation, which usually employs dynamic optical components, interferometric setups, and/or multiple bulky elements in cascade. A very efficient solution is provided by metalenses, which are flat optical elements able to generate and manipulate structured light beams in a compact and efficient way, offering a powerful and attractive tool in many fields, such as life science and telecommunications. In this work, we present the design and test of transmission dielectric bi-functional metalenses that exploit both the dynamic and the geometric phases, to enable the spin-controlled manipulation of different focused OAM beams, depending on the circularly polarized state in input. In detail, we provide numerical algorithms for the design and simulation of the meta-optics in the telecom infrared, the fabrication processes, and the optical characterization under different impinging polarized optical vortices. This solution provides new integrated flat optics for applications in imaging, optical tweezing and trapping, optical computation, and high-capacity telecommunication and encryption.